2015
DOI: 10.1111/jch.12597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the DASH Diet and Walking on Blood Pressure in Patients With Type 2 Diabetes and Uncontrolled Hypertension: A Randomized Controlled Trial

Abstract: Data on the potential beneficial effects of combining diet and exercise on blood pressure (BP) are still scarce. A 4‐week randomized controlled clinical trial was undertaken in 40 hypertensive patients with type 2 diabetes with uncontrolled blood pressure (BP) in office and daytime ambulatory BP monitoring (ABPM). Patients were assigned to follow a Dietary Approaches to Stop Hypertension (DASH) diet associated with advice to increase walking using a pedometer (intervention group) or a diet based on the America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 36 publications
4
106
1
3
Order By: Relevance
“…The results of a study by Paula et al . in 2015, which compared the effects of the DASH diet together with walking versus the ADA diet on patients with T2DM, showed that none of the two diets had a significant effect on HDL and TC . However, the DASH diet significantly reduced the TG and LDL levels while the effect of the ADA regimen was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study by Paula et al . in 2015, which compared the effects of the DASH diet together with walking versus the ADA diet on patients with T2DM, showed that none of the two diets had a significant effect on HDL and TC . However, the DASH diet significantly reduced the TG and LDL levels while the effect of the ADA regimen was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary advice for hypertension in diabetes4691011 has been mostly based on studies conducted in non-diabetic subjects578. In patients with type 2 diabetes, the beneficial association of the DASH diet with BP was previously demonstrated in both a cross-sectional study12 and clinical trials1314.…”
mentioning
confidence: 99%
“…Two additional DASH studies, also reporting ABPM, confirmed these findings and reported a lowering of systolic BP of between 9.5 and 15 mmHg in response to intervention [128,129]. The greatest lowering achieved (a mean reduction in systolic BP of 15 mmHg) reported by Paula et al is likely to be explained by the inclusion of an exercise component within this intervention [129]. …”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 81%
“…Other studies have reported that higher concentrations of serum calcium, phosphate and parathyroid hormone are associated with the non-dipping pattern in hypertensive patients without renal disease [126]. The majority of other studies failed to report the dipping pattern, mean arterial pressure, heart rate and/or pulse pressure despite the use of ABPM [127,128,129,130,131,132,133,134,135,136,137,138,139]. …”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 99%
See 1 more Smart Citation